Study on Contact Fatigue Life of Slewing Bearing of a Vehicle-borne Radar based on ANSYS Workbench - Hu Jian; Zhao Pengfei; Li Gangyan; Sun Qipeng (Jixie chuandong)
Aiming at the failure of slewing bearing in a certain type of vehicle-borne radar actuator，the service life of slewing bearing is studied according to its structural characteristics and operating conditions，and a life prediction method of slewing bearing based on finite element method is obtained. Using ANSYS Workbench to analyze the simplified three-dimensional model of slewing bearing，the contact stress and fatigue life of inner and outer raceway and rolling body of slewing bearing are obtained，which improves the calculation efficiency. The accuracy of the finite element method is verified by comparing the results of the finite element method with those of the Hertz contact theory and the actual work.